Aerospace airflow and transient elastodynamic responses of the smart composite structures: Verification of the results via a machine learning algorithm - Ru, Yi; He, Junda; Wang, Mengxia; Wang, Fushuai; Sharaf, Mohamed (Aerospace science and technology, 2025)
•Smart composite panels with TPMS core effectively suppress airflow and shock-induced vibrations.•Integrated piezoelectric sensor-actuator layers enable real-time control of structural vibrations.•Constant-gain negative velocity feedback enhances vibration damping in curved composite panels.•Hybrid-estuary box algorithm offers efficient control with reduced computational cost.•Verified control strategy supports aerospace applications with intelligent, adaptive performance. This study presents an intelligent control strategy for mitigating vibrations induced by external shocks on sandwich doubly curved panels with a Triply Periodic Minimal Surface (TPMS) core and piezoelectric face sheets. The sandwich panel system, equipped with piezoelectric materials as both sensor and actuator layers, is subject to external excitations, including airflow pressure and mechanical shocks, which induce undesired vibrations. To enhance vibration damping, a constant-gain negative velocity feedback control method is applied. This approach is modeled and analyzed using the Laplace transform method to derive precise dynamic responses of the system. Furthermore, a novel hybrid-estuary box algorithm is introduced for effective optimization and control, aimed at minimizing computational cost while maintaining high performance in vibration suppression. The results from the hybrid-estuary box algorithm are validated through a detailed mathematical simulation, which demonstrates its potential for future applications in dynamic control systems. The proposed controller efficiently mitigates the vibrational effects while offering a low computational cost, making it an ideal solution for practical applications in advanced structural engineering, particularly in aerospace and civil engineering domains. This research contributes to the development of intelligent control systems for complex structural elements, providing valuable insights into the integration of smart materials and algorithms for enhanced performance and reliability.